A survey assessing methods of maintaining denture hygiene among denture wearers - Ghimire, B; Dhital, S (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: This study aimed to investigate the denture hygiene habits among old age denture wearers. The purpose of the study was to explain about the methods of maintaining denture hygiene among denture wearers. Methods: The present cross-sectional survey was conducted among denture wearer patients during follow-up appointment, using a self-administered structured questionnaire. Results: The study sample consisted of a total of 324 participants; out of them, 211 (65.1%) were males and 113 (34.9%) were females. Regarding the method of maintaining denture cleanliness, most of the patients cleaned it with water only (57.1%), whereas patients who cleaned with brush and paste were less (35.8%) and very few cleaned it with a combination of water, brush and toothpaste (7.1%). Conclusion: Majority of the patients cleaned their denture at least once daily and were provided with proper instructions from their dentist to maintain denture hygiene.